1999
DOI: 10.1002/(sici)1097-4628(19991128)74:9<2234::aid-app12>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of irradiated isotactic polypropylene

Abstract: ABSTRACT:The research in this article explores the response of semicrystalline isotactic polypropylene to gamma radiation in air, and relates the morphological changes of the polymer to corresponding changes in mechanical properties. The effect of the initial morphology of the polymer on its response to irradiation is considered using infrared spectroscopy (FTIR), small-and wide-angle X-ray scattering, dynamic mechanical thermal analysis (DMTA), and mechanical testing. The extent of chain scission and crosslin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 18 publications
2
13
0
1
Order By: Relevance
“…The extent of chain scission and crosslinking of PP is dependent on the -irradiation dose but not the initial starting morphology (Zhang and Cameron 1999). Using WAXD (Wide angle X-ray diffraction) and DSC (Differential scanning calorimetry) techniques, Alariqi et al (2006) found change in the degree of crystallinity, which caused by -irradiation, depends on the -irradiation dose ( see Table 6) and Kostoski and Stojanovic (1995) found the increase in crystallinity of oriented isotactic polypropylene with low absorbed doses of -radiation, up to 200 kGy.…”
Section: Fig 8 Radiolytic Degradation Of Pmmamentioning
confidence: 99%
“…The extent of chain scission and crosslinking of PP is dependent on the -irradiation dose but not the initial starting morphology (Zhang and Cameron 1999). Using WAXD (Wide angle X-ray diffraction) and DSC (Differential scanning calorimetry) techniques, Alariqi et al (2006) found change in the degree of crystallinity, which caused by -irradiation, depends on the -irradiation dose ( see Table 6) and Kostoski and Stojanovic (1995) found the increase in crystallinity of oriented isotactic polypropylene with low absorbed doses of -radiation, up to 200 kGy.…”
Section: Fig 8 Radiolytic Degradation Of Pmmamentioning
confidence: 99%
“…The ductile-brittle transition rises dramatically with irradiation, while the glass transition shows only a small increase. This observation is explained by irradiation, through chain scission and cross-linking, having a dominant effect on large-scale plastic deformation and a lesser effect on the deformation which relies on the amorphous phase alone [Zhang & Cameron, 1999].…”
Section: Polymeric Materials: Resin and Fibersmentioning
confidence: 99%
“…Research concerning to the micro-mechanical deformation mechanisms of irradiated and non-irradiated isotactic polypropylene (iPP), studied as a function of temperature above the glass transition has been reported [Zhang & Cameron, 1999]. Several deformation mechanisms were identified and included lamellar separation, shear, stable and unstable fibrillated deformation and cavitation.…”
Section: Polymeric Materials: Resin and Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires a thorough understanding of the effects of radiation on variety of polymers. A literature survey indicates that most of the work on the radiation effects on polymers focuses on a single macromolecule, leaving no scope for comparison, otherwise in a few reports the polymers with same class are compared (4)(5)(6)(7)(8)(9)(10)(11)(12). To the best of our knowledge, no report is found which focuses on the comparative studies on macromolecules belonging to quite different classes, but irradiated with the same radiation and under identical conditions.…”
Section: Introductionmentioning
confidence: 99%